Persistent gliding waterframe: the waterframe conceptual project - Morgado, João Paulo Salgueiro (2015)
Underwater gliders are autonomous vehicles that profile vertically by controlling buoyancy and move horizontally due to its wings.[14,17] At the top of a bounce, the glider decreases its buoyancy, which causes it to begin to sink. As the glider sinks, the hydrodynamic shape of the exterior (waterframe design) produces horizontal motion. The gilder uses a method of control to adjust pitch and roll as it continues forward. At the bottom of a bounce, the glider becomes more buoyant, which causes it to begin an upward path. Again, horizontal motion is produced by the shape of the waterframe and mainly by wings. When the glider reaches the surface, it will communicate with a ground station, sending out the data it collected during the dive and receiving instructions for its next trajectory.[5] This type of vehicles can operate over long ranges and are relatively low cost [2] ocean research vehicles, making them the ideal choice for locate potential areas in the ocean that would be suitable for sea farming. The PGW will be equipped with sensors that will monitoring the underwater environment. The data collected from the PGW will help researchers monitor the fish population and even implement sea farming. The driving customer requirements for the PGW include a four-month continuous operational runtime, the ability to produce a lower cost system than the current competitors, a two-year useful life before refitting, the ability to launch and recover the PGW from a boat or a dock, the ability to reach a maximum depth of 300 meters, the ability to navigate within 1000 meters of the PGW’s intended course, and all fluids contained in the PGW must be biodegradable. This thesis presents the development of the waterframe for small (75 Kg, 2,00m long) autonomous underwater vehicle with operating speeds about and ranges up to 3000 Km . A half scale prototype was built and performance tests need to be done to evaluate waterframe's performance.